1991
DOI: 10.1111/j.1365-2133.1991.tb00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial leucocyte adhesion molecule-1 (ELAM-1) expression in cutaneous inflammation

Abstract: Endothelial leucocyte adhesion molecule-1 (ELAM-1) is a recently described endothelial surface glycoprotein which is inducible by interleukin 1 (IL-1), tumour necrosis factor-alpha (TNF-alpha) or bacterial lipopolysaccharide (LPS). Using an immunohistochemical technique and a monoclonal antibody (1.2B6) specific for ELAM-1 we have found marked vascular endothelial expression of ELAM-1 in many cutaneous inflammatory disorders, including allergic contact dermatitis, atopic dermatitis and psoriasis, and in dermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(79 citation statements)
references
References 25 publications
3
76
0
Order By: Relevance
“…5 suggest that IFN␥ may also mediate a stress-induced enhancement of skin DTH by enhancing the recruitment, activation, and͞or effector function of leukocytes. With respect to leukocyte recruitment, numerous studies have shown that intradermal administration of IFN␥ to normal human skin (in doses similar to those applied in our studies) induces a significant increase in the expression of cell adhesion molecules, such as L-selectin (CD62-L), lymphocyte function-associated antigen (LFA-1), and intercellular adhesion molecule (ICAM-1), on endothelial cells (49,50), leukocytes (51,52), and keratinocytes (53), with ICAM-1 expression occurring first on endothelial cells and later on keratinocytes (54). With respect to leukocyte activation, low levels of corticosterone have been shown to potently enhance the early stages of T cell activation and T lymphocyte proliferation (55).…”
Section: Dhabhar Et Almentioning
confidence: 99%
“…5 suggest that IFN␥ may also mediate a stress-induced enhancement of skin DTH by enhancing the recruitment, activation, and͞or effector function of leukocytes. With respect to leukocyte recruitment, numerous studies have shown that intradermal administration of IFN␥ to normal human skin (in doses similar to those applied in our studies) induces a significant increase in the expression of cell adhesion molecules, such as L-selectin (CD62-L), lymphocyte function-associated antigen (LFA-1), and intercellular adhesion molecule (ICAM-1), on endothelial cells (49,50), leukocytes (51,52), and keratinocytes (53), with ICAM-1 expression occurring first on endothelial cells and later on keratinocytes (54). With respect to leukocyte activation, low levels of corticosterone have been shown to potently enhance the early stages of T cell activation and T lymphocyte proliferation (55).…”
Section: Dhabhar Et Almentioning
confidence: 99%
“…The first step of recruitment of leukocytes to the skin is the attachment of circulating cells to vascular endothelial cells, which is mediated by cell adhesion molecules, such as ICAM-1, VCAM-1, and Eselectin (21). It has been shown that the expression of these cell adhesion molecules is increased on dermal vessels of psoriatic skin (22)(23)(24)(25). To test the effect of miR-31 on endothelial cell-activating capacity of keratinocytes, we measured the expressions of ICAM-1, VCAM-1, and E-selectin in primary HUVECs incubated with culture medium from miR-31 inhibitor-treated keratinocytes.…”
Section: Mir-31 Regulates the Production Of Inflammatory Mediators Inmentioning
confidence: 99%
“…For example, a report by Ohkubo et al (1991) indicated that, under control conditions, leucocyte adhesion to microvascular endothelium in VX2 carcinoma was lower than that in normal tissues. Groves et al (1991) reported that while the expression Eselectin was present on the endothelial cells of squamous cell carcinomas, it was undetectable on vessels of basal cell carcinoma. Kuzu et al (1993) reported that the expression of several important adhesion molecules for leucocyte adhesion (i.e.…”
Section: C3mentioning
confidence: 99%